Peran Mediasi MargPeran Mediasi Margin Laba Bersih pada Faktor Internal terhadap Rentabilitas Perusahaan Sektor Teknologi yang Terdaftar di BEI Tahun 2021-2024 in Laba Bersih pada Faktor Internal terhadap Rentabilitas Perusahaan Sektor Teknologi yang Terdaftar di BEI Tahun 2021-2024 - Rihadatul Aisy, Salma; Waskito, Jaka; Amirah, Amirah (ILTIZAM Journal of Shariah Economics Research, 2025)
This inquiry examines the repercussions of Working Capital Turnover, Activity, Liquidity, and Inventory Turnover on Profitability, positioning Net Profit Margin as a mediator within technology enterprises listed on the Indonesia Stock Exchange (2021–2024). A quantitative framework was employed on secondary data sourced from the IDX portal utilizing multiple linear regression and path analysis. Pivotal outcomes elucidate: (1) Partially, Working Capital Turnover manifests no significant bearing on Net Profit Margin or Profitability; Activity exerts a substantially adverse effect on Net Profit Margin yet remains neutral toward Profitability; Liquidity demonstrates significantly positive associations with both variables; Inventory Turnover exhibits markedly negative impacts on Net Profit Margin and Profitability; whereas Net Profit Margin itself evinces no correlation with Profitability; (2) Path analysis discloses Net Profit Margin's efficacious mediation between Working Capital Turnover and Profitability, yet identifies its ineffectiveness in mediating the influences of Activity, Liquidity, and Inventory Turnover upon Profitability.